PS–ABC: A hybrid algorithm based on particle swarm and artificial bee colony for high-dimensional optimization problems - Li, Zhiyong; Wang, Weiyou; Yan, Yanyan; Li, Zheng (Expert systems with applications, 2015)
•A hybrid algorithm (PS–ABC) based on PSO and ABC is proposed.•PS–ABC examines the aging degree of pbest to decide which type of search phase.•Particle swarm optimization (PSO) serves as a local search phase.•Onlooker and modified scout bee from the ABC serves as two global search phases.•Our algorithm is effective in solving high-dimensional optimization problems. Particle swarm optimization (PSO) and artificial bee colony (ABC) are new optimization methods that have attracted increasing research interests because of its simplicity and efficiency. However, when being applied to high-dimensional optimization problems, PSO algorithm may be trapped in the local optimal because of its low global exploration efficiency; ABC algorithm has slower convergence speed in some cases because of the lack of powerful local exploitation capacity. In this paper, we propose a hybrid algorithm called PS–ABC, which combines the local search phase in PSO with two global search phases in ABC for the global optimum. In the iteration process, the algorithm examines the aging degree of pbest for each individual to decide which type of search phase (PSO phase, onlooker bee phase, and modified scout bee phase) to adopt. The proposed PS–ABC algorithm is validated on 13 high-dimensional benchmark functions from the IEEE-CEC 2014 competition problems, and it is compared with ABC, PSO, HPA, ABC–PS and OXDE algorithms. Results show that the PS–ABC algorithm is an efficient, fast converging and robust optimization method for solving high-dimensional optimization problems.